Kontribusi Organizational Commitment dan Perceived Organizational Support terhadap Organizational Citizenship Behavior pada Karyawan Generasi Milenial - Yolanda Caroline; Benedicta Prihatin Dwi Riyanti (Atma Jaya Catholic University of Indonesia, 2025)
Technological advancements in Society 5.0 have integrated humans with technology, encouraging millennials to prioritize their careers, maintain work-life balance, and pursue growth. A study involving 198 millennial employees (aged 24–43, each with at least two years of full-time work experience) investigated the impact of organizational commitment and perceived organizational support on organizational citizenship behavior (OCB). The results showed that while affective commitment and perceived organizational support significantly influenced OCB, continuance and normative commitments did not. These findings suggest practical implications for organizations seeking to enhance OCB among millennial employees. Specifically, developing targeted programs to strengthen affective commitment and enhance perceived organizational support – by making it more tangible and impactful for employees – can serve an effective strategy for fostering positive organizational behavior.